Cell-mediated targeting drugs delivery systems - Hongli Yu; Zhihong Yang; Fei Li; Lisa Xu; Yong Sun (Taylor & Francis Group, 2020)
Drug delivery systems have shown tremendous promise to improve the diagnostic and therapeutic effects of drugs due to their special property. Targeting tissue damage, tumors, or drugs with limited toxicity at the site of infection is the goal of successful pharmaceuticals. Targeted drug delivery has become significantly important in enhancing the pharmaceutical effects of drugs and reducing their side effects of therapeutics in the treatment of various disease conditions. Unfortunately, clinical translation of these targeted drug delivery system mechanisms faces many challenges. At present, only a few targeted drug delivery systems can achieve high targeting efficiency after intravenous injection, even though numerous surface markers and targeting approaches have been developed. Thus, cell-mediated drug-delivery targeting systems have received considerable attention for their enhanced therapeutic specificity and efficacy in the treatment of the disease. This review highlights the recent advances in the design of the different types of cells that have been explored for cell-mediated drug delivery and targeting mechanisms. A better understanding of cell biology orientation and a new generation of delivery strategies that utilize these endogenous approaches are expected to provide better solutions for specific site delivery and further facilitate clinical translation.